A responsabilidade do analista e sua prática no hospital - Marques, Gardênia Holanda (2015)
Psychoanalysts have begun to work at hospital institutions predominantly in late 70s. Various academic productions that deal with the relationship between psychoanalysis and its clinical work in the hospital point to an issue that emerge from the practice of each analyst inserted in this space, an issue that emerge from their relationship with desire. We consider that analytic listening, as a tool used to allow patients a different way to elaborate their suffering, brings into account the analyst's responsibility to sustain their praxis. In this perspective, this paper aims to conduct a study on the notion of responsibility for psychoanalysis and to question its challenges in hospital institutions facing the hegemony of the medical discourse, considering that the sustenance of psychoanalysis’ act becomes possible through transference relationship. The method used to achieve these goals was literature review and the study of clinical vignettes. We also performed a study on the state of knowledge of the productions of the last decade on psychoanalysis and hospital; then we have elaborated the notion of responsibility for psychoanalysis and contextualized the practice of the analyst in the hospital. We have finished the survey with vignettes that put into question the responsibility of the analyst and its effects. The results of this research imply that the responsibility of the analyst is in relation to the unconscious and that the position of the analyst and his ethics can provide access to a knowledge of the unconscious.